Asuhan Kebidanan Komprehensif Pada Ny. R Umur 41 Tahun Grandemultipara Dengan Obesitas Di Puskesmas Buaran Kabupaten Brebes Tahun 2024 - Nurjuliana; Himatul Khoeroh; Nur Hidayah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Pregnancy at age ≥35 years with grandemultipara (5th pregnancy) has a high risk of obstetric complications, especially accompanied by obesity. The combination of these three factors can increases the risk of preeclamsia, gestational diabetes, prolonged labor, postpartum hemorrhage, congenital hearth disease in the fetus and other complications. To monitor and prevent complications in pregnancy, childbirth, postpartum, newborns and family planning. This study uses a qualitative descriptive research method with a comprehensive study approach. Based on the results obtained, problems were found at the 1st pregnancy visit, namely a BMI of 32 m/kg2, then an Hb level of 8.9 g/dl at the 2nd pregnancy visit and mild preeclampsia with BP examination results: 140/98 mmHg, urine protein +1 accompanied by swelling in both legs at the 3rd pregnancy visit. Mrs. R’s delivery was carried out by cesarean section along with a sterilization. Mrs. R’s baby was born normally and no problems were found during the postpartum period.From the comprehensive midwifery care that has been provided and the problems encountered have been implemented and resolved well